Elaboración de un plan de mantenimiento para una máquina piloteadora CMV TH 15/50 de la empresa Disepil S.A.S. (2020)
The main objective of this project is to elaborate a maintenance plan for a CMV TH 15/50 piling machine from the company DISEPIL S.A.S. This seeks to obtain the highest availability of equipment, reduce recurring failures to the maximum, improve performance on site, avoid downtime due to unscheduled stops, avoid cost overruns and increase profitability in projects where the CMV TH 15 pile driver is used.